Coupled magnetic and elastic properties in LaPr(CaSr)MnO manganites - Eslava, G.G. (2016)
We investigate a series of manganese oxides, the La0.225Pr0.4(Ca1−xSrx)0.375MnO3 system. The x=0 sample is a prototype compound for the study of phase separation in manganites, where ferromagnetic and charge ordered antiferromagnetic phases coexist. Replacing Ca2+ by Sr2+ gradually turns the system into a homogeneous ferromagnet. Our results show that the material structure plays a major role in the observed magnetic properties. On cooling, at temperatures below ∼100 K, a strong contraction of the lattice is followed by an increase in the magnetization. This is observed both through thermal expansion and magnetostriction measurements, providing distinct evidence of magneto-elastic coupling in these phase separated compounds.